The Democratic Imagination in America : Conversations with Our Past - Hanson, Russell L., 1953- (Book collections on Project MUSE., 1985)
Russell Hanson discovers in the history of democratic rhetoric in the United States a series of essential contests" over the meaning of democracy that have occurred in periods of political and socio-economic change. Originally published in 1985. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905